GM-CSF as a target in inflammatory/autoimmune disease: current evidence and future therapeutic potential. (April 2015) - Hamilton, John A
<x xml:space="preserve">Abstract</x> Granulocyte-macrophage colony-stimulating factor (GM-CSF) can be viewed as a pro-inflammatory cytokine rather than as a key regulator of steady state and systemic myelopoiesis. Key aspects of GM-CSF biology need to be clarified such as pro-survival vs activation/differentiation function, its cellular sources, its responsive cell populations, its downstream mediators/pathways, and when GM-CSF is relevant. Striking effects of GM-CSF depletion/deletion in some pre-clinical autoimmune/inflammation models have been reported. Systemic effects of administered GM-CSF are not necessarily informative about its local blockade in disease. Recent clinical RA trials, particularly Phase II trials with mavrilimumab (anti-GM-CSFRα Ab), show rapid and impressive efficacy with no significant adverse effects. Larger and longer trials targeting GM-CSF are needed and with careful monitoring of unwanted side effects. This review summarizes the most recent information on these topics.